2018
DOI: 10.1080/19390211.2018.1472714
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Resveratrol and Mangiferin onPPARγandFALDHGene Expressions in Adipose Tissue of Streptozotocin-Nicotinamide-Induced Diabetes in Rats

Abstract: Type 2 diabetes (T2D) is characterized by insufficient insulin secretion by the pancreatic beta cells and insulin resistance in liver, skeletal muscle, and white adipose tissue. Adipose tissue plays a major role in glucose homeostasis and lipid metabolism. Dietary antioxidants such as resveratrol and mangiferin may offer some protection against the early stage of diabetes mellitus. Therefore, an attempt has been made to investigate the effects of resveratrol and mangiferin on biochemical parameters and molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…In addition, these antioxidant compounds frequently display actions on other factors implicated in diabetes, like inflammation, autophagy or β-cell proliferation [96,101,103,104,105]. A clear example is resveratrol, a polyphenol whose high antioxidant activity has been shown to prevent and protect against diabetes and its complications, as well as improving glucose homeostasis [106,107,108].…”
Section: Targeting Oxidative Stress In T2d: Evidence On the Use Ofmentioning
confidence: 99%
“…In addition, these antioxidant compounds frequently display actions on other factors implicated in diabetes, like inflammation, autophagy or β-cell proliferation [96,101,103,104,105]. A clear example is resveratrol, a polyphenol whose high antioxidant activity has been shown to prevent and protect against diabetes and its complications, as well as improving glucose homeostasis [106,107,108].…”
Section: Targeting Oxidative Stress In T2d: Evidence On the Use Ofmentioning
confidence: 99%
“…49 Meanwhile, the prevention and protective effects of MGF on diabetes and its complications caused by oxidative stress, ROS, and insulin resistance were also collected. 50,51 2.3 Clinical randomized controlled trials of mangiferin on diabetes and diabetic complications Various in vitro and animal studies have shown that the MGF intake could improve diabetes and its complications, including insulin sensitivity, glycolipid metabolism disorders, diabetic nephropathy, cardiovascular disease, and cognitive performance. [52][53][54][55] Nevertheless, the medical effects as well as the clinical effects and implications of MGF need to be further explored and studied.…”
Section: Animal Studies On the Effects Of Mangiferin On Diabetes And ...mentioning
confidence: 99%
“…PPARγ activation also increases antioxidant defence and regulates mitochondrial function [62]. FALDH is an enzyme that can metabolise 4-hydroxynonenal (HNE) and decrease HNE-induced ROS production [63]. Curcumin is a polyphenolic compound that has been shown to have anti-hyperglycaemic, anti-inflammatory, and antioxidant activity, attenuating DM complications [98].…”
Section: Natural Polyphenolsmentioning
confidence: 99%